RISK ANALYSIS AND RISK MONITORING FOR PROJECT: CASE STUDY ON CONVEYOR CONSTRUCTION PROJECT - Prilly Febi Pratiwi; Taufik Faturohman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
PT Bukit Asam Tbk has ambitious production and sales targets for its long-term planning. Meanwhile, research shows that coal prices tend to be stable and declining, while oil prices tend to rise. The condition requires PTBA to maintain control over production costs and maximize profits. To improve production efficiency, reengineering is necessary to achieve the lowest possible production costs while maximizing output. One of PTBA’s efforts to improve production efficiency is the construction of an in-mine conveyor, a solution for coal handling, which currently relies on trucking for this route. Ensuring sufficient capital expenditure is crucial to project success. In addition to commitment from all parties, consistent risk management is also necessary to identify and mitigate potential risks that could derail project objectives. However, it is understood that, under current conditions, the project’s risk management practices are not yet integrated or comprehensive. A gap analysis was conducted to assess the effectiveness of PTBA’s current project risk management implementation, comparing it with international standards (ISO 31000:2018) and PTBA procedures. The study revealed that risk management in the PTBA project was not yet well established, as evidenced by risks not identified in the initial risk list. The risk analysis process was not comprehensive, as evidenced by the continued reliance on qualitative expert assessments despite the availability of quantifiable data. Furthermore, risk prioritization was not carried out, leading to all risks being mitigated, even those considered low or low to moderate, and a lack of focus on significant risks. Furthermore, monitoring for the conveyor project within the mine was inconsistent. Recognizing this alignment, a re-identification was conducted by first compiling an analysis document of the project’s internal and external factors using the 5M (People, Machines, Methods, Money, Materials) and PESTEL (Political, Economic, Social, Technological, Environmental, and Legal) analysis. A risk analysis of the conveyor project’s risk levels within the mine was conducted, specifically calculating their impacts and simulating them in a financial model to determine the project’s NPV and IRR. Next, risk prioritization was undertaken to identify the Project’s Key Risks. Furthermore, a mitigation plan was developed, including the Project Implementation Unit (PIC), outputs/deliverables, and timeframe. In addition, key risk indicators (KRIs) are designed to provide early warning signs for each risk. Routine monitoring of these Key Risks is planned at least once a month, with more frequent monitoring if needed.